Pengaruh Kebiasaan Sarapan Terhadap Konsentrasi Belajar Anak Sekolah Dasar - Dia Rejeki Utami; Andi Ernawati Manuntungi; Nuryanti Thahir (Barongko: Jurnal Ilmu Kesehatan, 2026)
Breakfast is one of the eating habits that plays an important role in providing energy for the body, especially for school-aged children who require optimal concentration during learning activities. This study aimed to determine the effect of breakfast habits on learning concentration among elementary school children. This research used a quantitative method with a cross-sectional design. The sample consisted of 60 elementary school students selected using purposive sampling techniques. Breakfast habits were measured using questionnaires, while learning concentration levels were assessed through observation instruments. Data were analyzed using statistical tests to determine the relationship between breakfast habits and learning concentration. The results showed that children who regularly consumed breakfast had better learning concentration compared to children who did not regularly eat breakfast. The analysis indicated that breakfast habits were associated with learning concentration among elementary school children. Regular breakfast consumption can help fulfill energy and nutritional needs, thereby supporting cognitive function, attention, and learning activities.